EFEKTIVITAS KOMUNIKASI PROSES PEMBELAJARAN JARAK JAUH (DARING) - Eka Widyaningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2020)
Title: Communication Efficacy During Distance Learning Process (Online) The Coronavirus pandemic has been forcing us to avoid physical contact in the working field and educational institutions. We have to deal with many ostacles in this new learning and working environment, both technical and non-technical. Unstable internet connectivity and the financial challenge to provide online access for students at home are among the fundamental problems caused by this distance learning process. As a consequence of this study, material delivery and student’s comprehension are at risk. Based on these facts, lecturers and institutions must have proper/ better planning strategies to increase learning outcomes in an academic program as a whole and each course for more aimed results. In an architecture department, studio courses are essential. One strategy example of dealing with today’s situation is a collaboration among 2-3 studio courses on the same level to enhance mutual achievement, creating better synergy between methods. This learning strategy’s objective is to make the learning process delivery more efficient and comprehensible to students.